Sex as an independent risk factor for cerebellar mutism syndrome: a validation study - Peng, Xiaojiao; Zhi, Zhuo; Chai, Xinyi; Zhang, Hong; Cai, Yingjie; Zhu, Kaiyi; Zhang, Nijia; Wang, Jia; Sun, Hailang; Yin, Guangheng; Ma, Wenping; Yang, Wei; et al. (Frontiers in Surgery, 2025)
BackgroundCerebellar Mutism Syndrome (CMS) is a significant neurological complication following posterior fossa tumor surgery in children. The pathophysiological mechanisms of CMS remain elusive, and there is a growing interest in the potential influence of sex on its incidence. This study aims to evaluate sex as an independent risk factor for the development of CMS.MethodsA retrospective cohort study of 385 pediatric patients who underwent posterior fossa tumor surgery at Beijing Children's Hospital (2013–2024) was conducted. Comprehensive demographic, clinical, and pathological data were collected. Statistical analysis involved Chi-square tests for categorical variables, Kruskal–Wallis tests for non-parametric comparisons among groups, and logistic regression to identify independent predictors of CMS.ResultsCMS occurred in 29.9% of all cases, with annual incidence ranging from 14.3% to 37.9%. Medulloblastoma was the most common pathology (38.4%), with a median maximal tumor diameter of 47.2 mm. Tumors were predominantly located at the midline (68.1%), and gross total resection was achieved in 86.3% of patients. Male patients exhibited a significantly higher incidence of CMS compared to females (73.0% vs. 53.0%, p = 0.003). Independent risk factors for CMS included male sex [OR 2.25; 95% CI (1.30–3.70)], midline tumor location [OR 7.47; 95% CI (2.79–19.98)], and medulloblastoma diagnosis [OR 2.11; 95% CI (1.24–3.59)].ConclusionThis study indicates a notable male predominance in CMS occurrence, suggesting the existence of sex-specific differences in cerebellar function and language development. These findings highlight the need for heightened monitoring and tailored interventions for male patients undergoing posterior fossa tumor surgery and suggest a potential biological basis for sex-specific differences in cerebellar function and vulnerability to surgical injury.Importance of the studyThis study provides critical insights into the significant role of sex as an independent risk factor for Cerebellar Mutism Syndrome (CMS) following posterior fossa tumor surgeries in pediatric patients. By identifying male sex, midline tumor location, and medulloblastoma pathology as independent predictors, this research addresses a gap in understanding sex-based disparities in CMS development. These findings suggest potential gender-specific differences in cerebellar and language development, offering a foundation for future translational research and targeted clinical strategies. The results emphasize the need for heightened monitoring and tailored interventions, especially for male patients, to mitigate CMS risk and improve surgical outcomes in pediatric neurosurgery.